Kaposi's sarcoma: Genetic subtypes and clinical correlation in a South African population - Isaacs, Thuraya (Division of Dermatology, 2017)
Human herpes virus 8 (HHV8) is the aetiological agent of all forms of Kaposi's sarcoma (KS). Seven major subtypes (A, B, C, D, E, F, Z) based on genetic variability of open reading frame (ORF)-K1, have been identified. Numerous studies point to differing tumorigenic and pathogenic properties of the HHV8 subtypes. The study objective was to determine the prevalence of the HHV8 subtypes in a cohort of clinical and histologically confirmed KS in Cape Town, South Africa, and analyse associations between the different subtypes, clinico- epidemiological forms and clinical presentation of KS. The clinical data was prospectively collected and recorded on a body diagram and with photographs. Demographic data was retrospectively collected from clinical records. Tissue biopsies were taken for ORF-K1 subtyping. Out of a cohort of 103, eighty six patients were subtyped; 81 AIDS (aquired immune deficiency syndrome)-KS and 5 African endemic. Subtype A5 (42/86) and B2 (16/86) predominated. B1, B3, A1 and A4 subtypes were identified in 10/86, 9/86, 4/86 and 1/86 patients respectively. A5, B1, B2 and B3 were found in African blacks and individuals of mixed ancestry, while subtypes A1 and A4 are found only in whites and individuals of mixed ancestry. Subtype A5 was associated with >10 KS lesions at presentation in the AIDS-cohort (32/38, p=0,050), but not in the African endemic patients (2/4, p=0,600). Subtypes A1 and A4 were less likely to be associated with poor risk tumour extension (p=0,031) and A1 was associated with lower likelihood of lower limb involvement (p=0,004).